R-Ras interacts with filamin a to maintain endothelial barrier function - Griffiths, G.S.; Grundl, M.; Allen III, J.S.; Matter, M.L. (Journal of cellular physiology, 2011)
The molecular mechanisms regulating vascular barrier integrity remain incompletely elucidated. We have previously reported an association between the GTPase R‐Ras and repeat 3 of Filamin A (FLNa). Loss of FLNa has been linked to increased vascular permeability. We sought to determine whether FLNa's association with R‐Ras affects endothelial barrier function. We report that in endothelial cells endogenous R‐Ras interacts with endogenous FLNa as determined by co‐immunoprecipitations and pulldowns with the FLNa‐GST fusion protein repeats 1–10. Deletion of FLNa repeat 3 (FLNaΔ3) abrogated this interaction. In these cells FLNa and R‐Ras co‐localize at the plasma membrane. Knockdown of R‐Ras and/or FLNa by siRNA promotes vascular permeability, as determined by TransEndothelial Electrical Resistance and FITC‐dextran transwell assays. Re‐expression of FLNa restored endothelial barrier function in cells lacking FLNa whereas re‐expression of FLNaΔ3 did not. Immunostaining for VE‐Cadherin in cells with knocked down R‐Ras and FLNa demonstrated a disorganization of VE‐Cadherin at adherens junctions. Loss of R‐Ras and FLNa or blocking R‐Ras function via GGTI‐2133, a selective R‐Ras inhibitor, induced vascular permeability and increased phosphorylation of VE‐Cadherin (Y731) and Src (Y416). Expression of dominant negative R‐Ras promoted vascular permeability that was blocked by the Src inhibitor PP2. These findings demonstrate that maintaining endothelial barrier function is dependent upon active R‐Ras and association between R‐Ras and FLNa and that loss of this interaction promotes VE‐Cadherin phosphorylation and changes in downstream effectors that lead to endothelial leakiness. J. Cell. Physiol. 226: 2287–2296, 2011. © 2010 Wiley‐Liss, Inc.